Influence of forest configuration and bird exclusion on insect herbivory in Indonesian oil palm smallholdings - DIMAS HARYO PRADANA; NURUL LAKSMI WINARNI; MUFTI PETALA PATRIA; YASMAN YASMAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pradana DH, Winarni NL, Patria MP, Yasman. 2025. Influence of forest configuration and bird exclusion on insect herbivory in Indonesian oil palm smallholdings. Biodiversitas 26: 4640-4646. The insect pest control services provided by birds may help address one biological challenge in oil palm plantations. Previous studies suggest that understory birds contribute to this ecosystem service and that forest configuration may influence their effectiveness. We investigated whether understory birds reduce insect pests and whether forest configuration affects their pest control services in six oil palm smallholdings in Indonesia. Understory birds were surveyed using the point count method at 0-200 m from adjacent forests. Herbivory rates, used as a proxy for insect pest activity, were assessed through a bird enclosure experiment. The indirect bird effect on herbivory rate was also evaluated using this experiment. We used binomial Generalized Linear Mixed Model (GLMM) to analyze the effects of understory bird abundance and forest configuration on herbivory rates. Results showed the herbivory rate ranged from 0.01 to 0.84 mm². A weak negative relationship between understory bird abundance and herbivory in control treatments (z: -1.65, n: 12, p-value<0.1) was found, suggesting a limited pest control effect. However, no significant influence of forest distance or remnant size on herbivory rates was observed. Functional trait analysis revealed that the bird community was dominated by gleaners, omnivores, and large-bodied species, which are typically associated with insectivores. The absence of strong effects may be linked to small forest remnant sizes, low pest abundance, and the structural limitations of smallholder oil palm understory that limit the use of this habitat by forest understory birds. While understory birds show some potential for insect pest control, their effectiveness appears constrained under current conditions. It is clear that urgent action is needed. Habitat enhancement through reforestation and vegetation management to increase habitat connectivity, and may be necessary to support more robust pest control by bird communities in oil palm landscapes.